WIDOW WOMEN’S RE-ESTABLISHMENT IN THE SOCIETY: A RESEARCH - Ms. Trusha Barot; Dr. Christina parmar (The Bioscan, 2024)
The social problems that widows encounter in every society are many and sometimes contradictory. Due to the fact that they are separated from their families and communities and are responsible for the care and maintenance of their children, their condition is characterised by a broad variety of linked aspects, including social, religious, cultural, and economic considerations. This is especially true in India, where societal and cultural standards dictate how people should spend their life and define the tasks that they are responsible for. Within the context of the family, the submissive status of women is mostly attributable to the persistent social and cultural standards that have been put in place. As the most fundamental human group, the family is the focal point of every person's life and the object of their loyalty. When it comes to the long-term viability of a culture, country, or state, the degree to which families are able to provide a genuine sanctuary for love and life is also an extremely important factor. It is very vital to have a family unit, regardless of whether it is a nuclear family consisting of a father, mother, and children or a nuclear family consisting of a husband, wife, and their individual children. In the event that each and every one of them was to stop working, there would be no one else who could take their position. Due to the absence of a main income earner, the mother would be confronted with a number of challenges and problems. In the event that it takes place via mortality, it would be a catastrophic event. The research tries to emphasis on the re-establishment of widow women in the society.